Academic entrepreneurship in China: individual human capital and institutional context in higher education organisations. Issue 1 (2nd January 2022) - Wang, Miao; Cai, Jianfeng; Munir, Hina
ABSTRACT: Drawing on the theory of complexity, the purpose of current research is to utilise fuzzy-set Qualitative Comparative Analysis (fs-QCA) to explore how casual configurations of academic scientists' human capital– scientific output, previous commercialisation experience, as well as institutional context, such as organisational scientific reputation, disciplines, entrepreneurial support and culture, lead to high individual intention in engaging in spin-off creations, patenting, licensing, contract research and consulting activities. Based on the samples in Chinese higher education organisations, the results revealed no single individual and institutional determinants alone are necessary to produce high academic entrepreneurial intention, while various configurations of these determinants will contribute to enhance academic entrepreneurial intention complementarily. Additionally, the findings also suggest significant divergence of different individual and institutional factors in explaining various commercialisation activities. These findings will provide theoretical insights for academic entrepreneurship literature and also add practical recommendations for policy makers.